Land drainage and flood defence responsibilities - Lutton, Melinda (Thomas Telford, 2010)
Looking at a range of issues concerned with the practice of land drainage and the legal implications associated with it, this text outlines responsibilities and statutes, as well as detailing the latest environmental guidelines.
Keywords: Drainage.; Drainage laws -- England.; Drainage laws -- Wales.; Flood control.; Flood control -- Law and legislation -- England.; Flood control -- Law and legislation -- Wales.; elektronické knihy; electronic books